Sonoelectrochemical nitrided graphene nanosheets with vacancies and their applications for catalysis and sensing of uric acid oxidation - Tzu-Chen Huang; Ying-Lung Chen; Mei-I Wu; Pei-Ssu Lin; Po-Yu Chen; Chien-Liang Lee (Ultrasonics Sonochemistry, 2023)
A sonoelectrochemical method for preparing N-doped defective graphene nanosheets (N/O-dGNs) with point defects and 5-9 or 5-8-5 vacancies and oxygen-containing groups was successfully demonstrated. In this one-pot approach, the N-bonding configuration and N content of N/O-dGNs were finely tuned by the ultrasonic power (192, 320, and 640 W). The N content in atomic percentage (at%) for N/O-dGN (N/O-dGN320W) with point defects and 5-8-5 vacancy prepared at 320 W power was 5.6 at%, greater than 3.0 at% and 2.6 at% for N/O-dGN with point defects and 5-9 vacancies at 192 W and 640 W power (N/O-dGN192W and N/O-dGN640W), respectively. N-bonding sites on N/O-dGN320W were dominantly amine N (2.1 at%) and pyrrolic N (2.4 at%). Additionally, the electrocatalytic activity of N/O-dGN192W, N/O-dGN320W, and N/O-dGN640W was successfully demonstrated for the sequential uric acid (UA) oxidation reaction (UOR), in which N/O-dGN320W displayed a significant mass activity (2.51 A/g). As in the transient catalysis of UOR, N/O-dGN320W with amine N showed 400.8 μA mM−1 cm−2 in sensitivity within a wide linear analysis range (1.5 × 10–2–6 mM) for amperometrically sensing UA. The results of real sample experiments using serum samples further demonstrated the potential of N/O-dGN320W as a non-enzymatic UA sensor.